Using Performance Appraisal as an Effective Tool for Motivating the Employees Performance: A Live Study. Issue 2 (January 2014) - Kumari, Neeraj
The study aims to find the impact of perceived fairness of performance appraisal on employee performance in telecom sector. The study is based on descriptive research. Data was collected from the respondents through a standardized questionnaire. Sample Unit consisted of 80 employees from Vodafone and Tata Docomo. Statistical analysis of the quantified data was done using SPSS software. The analysis of responses was done by using correlation and regression analysis. According to Correlation analysis there exists a relationship between perceived fairness of performance appraisal and employee performance. In regression analysis, the nature of the relationship between the dependent and the independent variables were analyzed and the result was that there exists a significant impact of perceived fairness of performance appraisal on employee performance. The study concludes that perceived fairness of performance appraisal behavior plays a very vital role in contributing to organizational functioning and performance thereby giving a better clarity to the relation between employee performance and perceived fairness of performance appraisal.